2020
DOI: 10.5811/westjem.2020.6.47032
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic Pain Management Practice with Introduction of a Non-opiate Treatment Protocol

Abstract: Introduction: There is concern about the initiation of opiates in healthcare settings due to the risk of future misuse. Although opiate medications have historically been at the core of prehospital pain management, several states are introducing non-opiate alternatives to prehospital care. Prior studies suggest that non-opiate analgesics are non-inferior to opiates for many acute complaints, yet there is little literature describing practice patterns of pain management in prehospital care. Our goal was to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Some studies have indicated that females are disproportionality treated less for their pain, even when the complaints of pain are similar to males. 37,38,[40][41][42][43][44] This may create an equity of care and patient safety problem in prehospital care, as female patients may go longer without adequate pain relief. This is important to note as some research shows that females experience more severe, longer lasting and recurrent pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have indicated that females are disproportionality treated less for their pain, even when the complaints of pain are similar to males. 37,38,[40][41][42][43][44] This may create an equity of care and patient safety problem in prehospital care, as female patients may go longer without adequate pain relief. This is important to note as some research shows that females experience more severe, longer lasting and recurrent pain.…”
Section: Discussionmentioning
confidence: 99%
“…All studies met the methodological quality rating threshold of 60% with four studies having a quality rating of 100%, 38,[40][41][42] seven having a quality rating of 75% 37,[43][44][45][46][47][48] and two having a quality rating of 62.5%. 39,49 All ROB scores are listed in Table 2.…”
Section: Risk Of Biasmentioning
confidence: 97%
See 2 more Smart Citations
“…The treatment of pain at the prehospital care level is a major concern in many healthcare systems all over the world [ 8 11 ], being one of the priority activities for paramedics [ 12 ]. The first large-scale analysis in Poland concerning application of pain assessment showed how often and in what situations paramedics use pain scales, what medications and whether multimodal analgesia they use and with what effect.…”
Section: Discussionmentioning
confidence: 99%